Da “intimidação intencional” aos “ciúmes excessivos”: uma análise linguística forense das Fichas de Avaliação de Risco - Ferreira, Ana Sofia; Sousa-Silva, Rui (Language and Law / Linguagem e Direito, 2020)
Domestic violence and its legal processing involve language to a large extent. In Portugal, one of the resources used to handle accusations of domestic violence is the Risk assessment forms (Fichas de Avaliação de Risco) – a set of 20 questions asked by the police or legal officer to the victim. This article presents the results of a forensic linguistic analysis of these questions. The analysis shows that these questions have several linguistic problems that may hamper the efectiveness of the risk assessment forms at the level of syntax, semantics, lexis/terminology and pragmatics/discourse. Consequently, the victim may misinterpret the questions, and their answer can in turn be misinterpreted by the officers. The level of risk for the victim can, as a result, be wrongly assessed and eventually jeopardise the victim’s safety.